Developing technological pedagogical content knowledge skills during teaching practicum - Muhamad Jaeni; Muhammad Ali Ghufron (Institute of Advanced Engineering and Science, 2024)
This study investigates the efforts of Indonesian pre-service teachers in developing their technological pedagogical content knowledge (TPACK) skills during teaching practicum, explores the obstacles they encounter in this process, and examines their responses to the challenges of TPACK skills development. Employing qualitative narrative inquiry as the research method, the study interviews five pre-service teachers from various study programs to gain insights into their experiences. The findings demonstrate that Indonesian pre-service teachers employ diverse strategies to enhance their TPACK skills, including observing experienced teachers, participating in workshops or online courses, reading relevant literature on TPACK, and consistently integrating TPACK into their teaching practice. However, they face obstacles such as a lack of confidence in their teaching abilities, limited time and resources for reflective practice, and inadequate self-awareness regarding their skills. To overcome these obstacles, they respond by collaborating with peers and mentors, engaging in reflective teaching practice, and setting goals for each practicum session. The study provides valuable insights for teacher training institutions (TTIs), educators, practitioners, and policymakers, facilitating the implementation of more effective strategies for integrating TPACK in future events.